Diagnostic role of fine needle aspiration cytology in breast lesion - Rakesh Pathak; Shreesti Adhikari; Bipin Maharjan; Monika Shrestha (Journal of Pathology of Nepal)
Background: Breast lesions are among the most common concerns presenting in surgical outpatient departments, often accompanied by anxiety over potential malignancy. Fine needle aspiration cytology offers a safe, reliable, and efficient diagnostic procedure that minimizes patient discomfort while providing rapid results.